Geografia da periferia urbana: lugar de múltiplas representações no entorno do trecho rodoviário Niterói-Manilha, BR 101 - Leila de Oliveira Lima Araujo (2014)
The present study analyses the urban periphery through the new image registered by the recent changes at the urban space. Traditionally, periphery has been regarded as the extramural space of the city, where the urban met the rural. Sometimes the concept blended up and mixed with the suburban, that occupied housing and industrial planned areas remote away from the inner cities and in the vicinity of railways and road. Though the concept of periphery is consolidated from the 1950s, when referring initially to countries with lower economic and distant focus of international decisions. Then, the concept was adapted and incorporated the definition of areas located beyond the city centers. Nowadays the space considered periphery is presented with landscapes that are not only the countryside when the city ends, plus also takes on another landscape that combines luxury condos, villas with spaces segregated and degraded, industries and trade in overall appearence in the vicinity of highways. As a recent phenomenom in Brazil, the study of periphery waas examinated through the place concept, learning that in this place life dialogues through local and global relations. In this way, we investigated the periphery in the vicinity of Niterói-Manilha highway (BR-101), located in the Metropolitan Region of Rio de Janeiro - RJ, where the construction of the trade and the arrival of overall appearance has brought changes to the lives of individuals in place. So, the study collected empirical data through newspaper articles, oral and directed interviews to uncover the construction of this urban landscape, and seek the perception of subjects in order to measure the spatial dynamics and social place.